2011
DOI: 10.1007/s11999-010-1676-y
|View full text |Cite
|
Sign up to set email alerts
|

Does Trochanteric Transfer Eliminate the Trendelenburg Sign in Adults?

Abstract: Level IV, therapeutic study. See the Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
(30 reference statements)
0
13
0
Order By: Relevance
“…Thirdly, we did not analyse the reliability of the Trendelenburg sign but elsewhere it has been shown to be reproducible with high kappa values. 52 And fourthly, there was a variable distribution of bone defects when compared with other studies, but we have reported on a full spectrum of defects. The modular revision stem was also used in femora with good bone (Paprosky type I and II defects) when a transfemoral approach was performed.…”
Section: Discussionmentioning
confidence: 62%
“…Thirdly, we did not analyse the reliability of the Trendelenburg sign but elsewhere it has been shown to be reproducible with high kappa values. 52 And fourthly, there was a variable distribution of bone defects when compared with other studies, but we have reported on a full spectrum of defects. The modular revision stem was also used in femora with good bone (Paprosky type I and II defects) when a transfemoral approach was performed.…”
Section: Discussionmentioning
confidence: 62%
“…Published results are not easily comparable because of the different rage of indications between authors. For example, a wide range [31] of improvement in hip abductors' insufficiency has been reported in the literature. This wide range is probably attributable to the variability of indications for surgery and to the etiology of deformity.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of patients with such morphologies have had a history of disturbance of the epiphyseal blood perfusion during conservative treatment of hip dysplasia, with early closure of the head physis and undisturbed growth of the trochanteric physis. Other etiologies, such as trauma or as a sequelae of an osteotomy, are also possible [31]. The clinical problem in the majority of such hips may be characterized by weakness of the gluteus medius muscle, but there is often also substantial pain and limitation of motion from impingement.…”
Section: Relative Neck Lengthening and Greater Trochanter Distalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…84,85 In addition, TPI has been described after total hip arthroplasty as a sequela of slipped capital femoral epiphysis and rarely after intertrochanteric osteotomies or in skeletal dysplasias. [86][87][88][89] Patients who place their hips at extremes of motion, such as ballerinas, may also experience TPI. 1 Any disease process that alters the relative relationship of the greater trochanter and ilium can lead to TPI.…”
Section: Trochanteric Pelvic Impingementmentioning
confidence: 99%